“Citizen journalism” and the myth of redemptive technology - Moretzsohn, Sylvia (Brazilian journalism research, 2015)
The objective of this article is to present a debate on the so called “citizen” journalism or “participatory journalism” and to demonstrate, among other points, the mistaken view of simply presenting a confrontation between “us” (citizens anxious to exercise freedom of expression) versus “them” (journalists trying hard to preserve their “privileged” role of informants). In this manner, I hope to contribute by off ering a new approach to this acclaimed revolution in journalism. If all of us could take on the role of journalists, journalism itself would be “naturalized”, or dissolved into daily errands. However, if we imagine a new scenario with the potential to change all of us into sources of news coverage, we might see that journalism has actually become more complex. Consequently, there is a demand for applying more rigorous criteria when selecting news stories. This concept, in turn, contradicts the current logic of “real time” journalism. However, that is a topic for an alto-gether different discussion.